ON IBN SINA’S TREATISE KITAB AL-SHIFA: A MUSICOLOGICAL PERSPECTIVE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article presents a detailed analysis of the musical theories expounded by Abu Ali Ibn Sina (Avicenna) in his encyclopedic treatise Kitab al-Shifa (“The Book of Healing”). As one of the most comprehensive philosophical and scientific works of the Islamic Golden Age, Kitab al-Shifa includes an entire section dedicated to music, titled Jamiʿ al-ʿilm al-musiqi (“The Compendium of Music Science”). Ibn Sina approached music as a mathematical science rooted in physical principles, yet also intertwined with human psychology, poetics, ethics, and aesthetics. This article outlines the structure and contents of the music section of Kitab al-Shifa, analyzes its theoretical underpinnings, and discusses its long-standing influence on both Islamic and Western musicology.